Redox Signaling from Mitochondria: Signal Propagation and Its Targets - Ježek, Petr; Holendová, Blanka; Plecitá-Hlavatá, Lydie (Biomolecules, 2020)
Progress in mass spectroscopy of posttranslational oxidative modifications has enabled researchers to experimentally verify the concept of redox signaling. We focus here on redox signaling originating from mitochondria under physiological situations, discussing mechanisms of transient redox burst in mitochondria, as well as the possible ways to transfer such redox signals to specific extramitochondrial targets. A role of peroxiredoxins is described which enables redox relay to other targets. Examples of mitochondrial redox signaling are discussed: initiation of hypoxia-inducible factor (HIF) responses; retrograde redox signaling to PGC1α during exercise in skeletal muscle; redox signaling in innate immune cells; redox stimulation of insulin secretion, and other physiological situations.
Keywords: Mitochondria; signální transdukce; Signal Transduction; reaktivní formy kyslíku; peroxiredoxiny; H2O2 diffusion; superoxidy; redox-regulation of kinases; Immunity; oxidace-redukce; Superoxides; mitochondrial superoxide formation; Hypoxia; mitochondrie; Protein Processing, Post-Translational; posttranslační úpravy proteinů; Reactive Oxygen Species; peroxiredoxins; imunita; hypoxie; Redox signaling from mitochondria; Peroxiredoxins; kosterní svaly; peroxid vodíku; Insulin-Secreting Cells; Muscle, Skeletal; Oxidation-Reduction; beta-buňky; Hydrogen Peroxide; HIF